2018
DOI: 10.1002/ccd.27583
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes after re‐entry device use for recanalization of common iliac artery chronic total occlusions

Abstract: This retrospective analysis found that recanalization of CIA occlusions using a RED is safe and is associated with long-term clinical outcomes similar to that of standard crossing techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Comparing re-entry devices (Pioneer and Outback) with standard crossing techniques; a retrospective study assessing long-term outcomes of common iliac arteries recanalization demonstrated similar target lesion revascularisation, major adverse limb events rates as well as complication rates. In this aforementioned study, Pioneer was used more often than Outback as it is less technically challenging (Kokkinidis et al, 2018 ). However, we cannot confidently conclude the superiority of one method, as there are no randomised control studies or prospective data collection, comparing the use of Pioneer with using crossing wires alone.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing re-entry devices (Pioneer and Outback) with standard crossing techniques; a retrospective study assessing long-term outcomes of common iliac arteries recanalization demonstrated similar target lesion revascularisation, major adverse limb events rates as well as complication rates. In this aforementioned study, Pioneer was used more often than Outback as it is less technically challenging (Kokkinidis et al, 2018 ). However, we cannot confidently conclude the superiority of one method, as there are no randomised control studies or prospective data collection, comparing the use of Pioneer with using crossing wires alone.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Kokkinidis et al ( 26 ) also published the first paper comparing long-term outcomes after PIER of CTOs of the AT with or without RED and they found non-significant differences among the two groups, as target lesion revascularization rate at 1 and 5 years was 11 and 29% with RED and 9 and 29% with traditional PIER, with a post-angioplasty stenting rate of 82% after RED and 87% after traditional PIER.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, open surgery has been the standard method for severe occlusive lesions, but recent advances in interventional techniques and devices allow percutaneous revascularization and present comparable patency rates during long follow-up for patients with iliac occlusive disease regardless of lesion complexity. As a result, this endovascular-first concept has been a regular concept in the majority of institutions worldwide [2,3].…”
Section: Introductionmentioning
confidence: 99%